Documentos sobre oficinas de correo "Postmaster" de Arroyo - Todd, Roberto H.; Work, Hubert; González, Hipólito; Padilla, José D.; Andújar, Manuel; Becerril, Joaquín A. (My University, 1921)
Documentos sobre oficinas de correo "Postmaster" de Arroyo.
Keywords: Postal service--Puerto Rico.; Servicio postal--Puerto Rico.; Salinas, Florencio; Guerrero, Oscar; Figuera, José Victor; Dávila, Juan C.; Partido Republicano (Puerto Rico); Republican party. Puerto Rico.